Hepatitis C virus infection among non-IDU HIV-infected and uninfected men who have sex with men. - Massimo Giuliani; Lorenzo Nosotti; Alessandra Latini; Concetta Mirisola; Fulvia Pimpinelli; Sabrina Volpi; Fabrizio Ensoli; Gianpaolo Impara; Guido Palamara (Mediterranean Journal of Hematology and Infectious Diseases)
In the Mediterranean countries, hepatitis C virus infection affect nearly 45% of HIV-1 infected individuals, consistently to the high proportion of patients with a history of intravenous drug use and exposed to the two viruses by parenteral route. Even in association with HIV-infection, HCV infection is rarely transmitted through sexual intercourse due to the lower efficiency of mucosal exposure to virus than that blood-borne. Thus, the incidence and prevalence of HCV infection are far lower among the non-intravenous drug users (IDU) at risk of sexually transmitted infections (STI). Two hypotheses may be taken in account to explain the lower prevalence rates observed in our seroprevalence study. The MSMs participating to our study could have less sexual contacts with IDU-MSMs than other gay community residents in other western countries. The non-IDU MSMs recruited in this study could have a lower frequency of at-risk sexual practices for HCV then the non-IDU MSMs enrolled in other studies.